2007
DOI: 10.1021/bi061749a
|View full text |Cite
|
Sign up to set email alerts
|

GM1 Specifically Interacts with α-Synuclein and Inhibits Fibrillation

Abstract: The aggregation of alpha-synuclein is believed to be a key step in the etiology of Parkinson's disease. Alpha-synuclein is found in the cytosol and is associated with membranes in the presynaptic region of neurons and has recently been reported to be associated with lipid rafts and caveolae. We examined the interactions between several brain sphingolipids and alpha-synuclein and found that alpha-synuclein specifically binds to ganglioside GM1-containing small unilamellar vesicles (SUVs). This results in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
209
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(236 citation statements)
references
References 77 publications
17
209
2
1
Order By: Relevance
“…Recently, Cremona et al (55) have shown that localization of the transporter in the cholesterol-rich membrane raft microdomains is essential for the AMPH-induced reversed transport of dopamine in dopaminergic neurons. GM1 (monosialotetrahexosylganglioside) is a well characterized membrane ganglioside that is distributed in the cholesterol-enriched membrane microdomains (56) and has been show to interact with and recruit ␣-synuclein to membrane rafts (57). We used confocal microscopy to examine the hypothesis that elevated ␣-synuclein affects the membrane microdomain distribution of DAT to regulate its activity.…”
Section: Dopamine Transporter and ␣-Synucleinmentioning
confidence: 99%
“…Recently, Cremona et al (55) have shown that localization of the transporter in the cholesterol-rich membrane raft microdomains is essential for the AMPH-induced reversed transport of dopamine in dopaminergic neurons. GM1 (monosialotetrahexosylganglioside) is a well characterized membrane ganglioside that is distributed in the cholesterol-enriched membrane microdomains (56) and has been show to interact with and recruit ␣-synuclein to membrane rafts (57). We used confocal microscopy to examine the hypothesis that elevated ␣-synuclein affects the membrane microdomain distribution of DAT to regulate its activity.…”
Section: Dopamine Transporter and ␣-Synucleinmentioning
confidence: 99%
“…␣-Syn interacts with phospholipid membranes and particularly with acidic phospholipids, a phenomenon attributed to the electrostatic attractions with the lysine residues found in the N-terminal region of the protein (17). Furthermore, ␣-Syn has been reported to associate with lipid rafts, lipid domains enriched in cholesterol and sphingomyelin, as well as with gangliosides (18,19). It has been shown that ␣-Syn binds small (20 -25-nm) unilamellar vesicles in preference to larger (125-nm) vesicles of a given composition (17).…”
Section: ␣-Synuclein (␣-Syn)mentioning
confidence: 99%
“…Interaction of a-syn with the ganglioside GM1, an essential component of the lipid rafts, has been proposed to mediate its recruitment to these structures. 66 This lipid raftmediated endocytosis has been proposed to mediate internalization of Ab peptide by primary neurons 67 and extracellular a-syn by microglial cells. 68 Whether such a mechanism could also mediate a-syn uptake by neuronal cells remains to be investigated (Figure 2b).…”
Section: Molecular Mechanisms Involved In Intercellular Transfer Of Amentioning
confidence: 99%